(untitled) (Revista Direito em Debate, 2020)
The article discussed the mediation and the labor compliance as complementary tools for prevention, management and consensual resolution of conflicts. The two tools gained strength in Brazil, particularly since the adoption of the Resolutions nº 125 of the CNJ and nº 174 of CSJT, and the approval of Law nº 12.846/2013, known as the Anti-Corruption Law. The main objectives were to demonstrate that mediation is not restricted to ensure access to justice, but actually serve as a mechanism of social participation of the citizen and proper handling of conflicts. It was also analyzed the compliance institute in the Brazilian legal system and the benefits of its implementation in the framework of companies. Based on a deductive method, based on a critical analysis of the doctrine and legislation on the matter, it was concluded that the mediation and compliance, acting together, can contribute both to the resolution of conflicts, when these have already occurred, as well as for its prevention, ensuring greater satisfaction to those involved and, consequently, a reduction in the filing of lawsuits and in high litigation before the Judiciary.